Sinomenine Confers Protection Against Myocardial Ischemia Reperfusion Injury by Preventing Oxidative Stress, Cellular Apoptosis, and Inflammation - Xia, Boyu; Li, Qi; Wu, Jingjing; Yuan, Xiaomei; Wang, Fei; Lu, Xu; Huang, Chao; Zheng, Koulong; Yang, Rongrong; Yin, Le; Liu, Kun; You, Qingsheng (Frontiers in Pharmacology, 2022)
Sinomenine (SIN), an alkaloid extracted from the root of S. acutum. sinomenine, has been shown to have antiarrhythmic, antioxidant, and anti-inflammatory effects in myocardial ischemia-reperfusion injury (MIRI) ex vivo. In this study, we investigated the cardioprotective effects of SIN in an in vivo mouse model of MIRI. Adult male C57BL/6J mice received SIN (80 mg/kg) for 5 days and underwent 30 minutes of percutaneous occlusion of the left anterior descending artery (LAD) followed by 24 hours of reperfusion. Results showed that pretreatment with SIN significantly reduced myocardial infarct size and concentrations of markers of cardiac injury and improved left ventricular ejection fraction (EF) and shortening fraction (FS) in MIRI mice. The SIN pretreatment prevented the MIRI-induced decrease in the expression levels of Bcl-2, increase in the expression levels of caspase-3, caspase-9, and Bax, and increase in the number of TUNEL-positive cells in ischemic heart tissue. It was also found that pretreatment with SIN prevented the MIRI-induced oxidative stress imbalance in ischemic heart tissue, as shown by the increase in total antioxidant capacity (T-AOC) and glutathione (GSH) and the decrease in malondialdehyde (MDA), reactive oxygen species (ROS), and dihydroethidium (DHE) density. Further studies showed that the stimulus of cardiac ischemia/reperfusion caused a remarkable increase in the expression levels of interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) mRNA in ischemic heart tissue, which was effectively prevented by pretreatment with SIN. These results demonstrate that SIN can attenuate MIRI-induced cardiac injury in vivo by preventing oxidative stress, inflammation, and apoptosis.